2020
DOI: 10.1021/acs.jpcc.0c01881
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Au Nanoparticles with Heteroleptic Cu(I) Diimine Complexes

Abstract: Gold colloidal nanoparticles (NPs) were functionalized in acetonitrile with a Cu­(I) complex consisting of one 2,2′-bipyridine ligand possessing a lipoic acid moiety and one 2,9-dimesitylene-1,10-phenanthroline. UV electronic absorption, inductively coupled plasma-atomic emission spectroscopy, and scanning transmission electron microscopy with energy-dispersive X-ray analysis specifically targeting the Cu element were employed to confirm the grafting of the metallic complex on the Au NPs via Au–S bond formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…They showed a decrease in ligand density with an increase in steric demand . Picardi et al demonstrated that a copper complex with a disulfide ligand (lipoic acid) can bind to the surface of 40 nm gold nanoparticles with a molecular footprint of 0.71 nm 2 . Ming et al found a molecular footprint of 0.24 nm 2 for pyrene-carrying thioesters and thiocarbonates on 12.5 nm gold particles .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed a decrease in ligand density with an increase in steric demand . Picardi et al demonstrated that a copper complex with a disulfide ligand (lipoic acid) can bind to the surface of 40 nm gold nanoparticles with a molecular footprint of 0.71 nm 2 . Ming et al found a molecular footprint of 0.24 nm 2 for pyrene-carrying thioesters and thiocarbonates on 12.5 nm gold particles .…”
Section: Resultsmentioning
confidence: 99%
“…77 Picardi et al demonstrated that a copper complex with a disulfide ligand (lipoic acid) can bind to the surface of 40 nm gold nanoparticles with a molecular footprint of 0.71 nm 2 . 78 Ming et al found a molecular footprint of 0.24 nm 2 for pyrene-carrying thioesters and thiocarbonates on 12.5 nm gold particles. 79 Ruks et al synthesized cysteine-functionalized ultrasmall gold nanoparticles.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Two classes of Cu­(I) bis -phenanthrolines engender either homoleptic or heteroleptic ligand topologies. Homoleptic cuprous phenanthrolines have been studied since the 1970s for their potent photoreducing capabilities, long-lived excited states, and tremendous durability to high-power laser excitation. ,, Heteroleptic complexes using diimine- and bis -phosphine-type ligands have been growing in interest, especially for applications in dye-sensitized solar cells, photoredox catalysis, and the construction of supramolecular donor–acceptor architectures. ,, The HETPHEN strategy leverages 2,9-mesityl-1,10-phenanthroline (mesPhen), ,, which is unable to form a bis -homoleptic complex but enables the binding of another suitable phenanthroline, assisted through π-interactions with the 2,9-mesityl substituents and the B-ring of the orthogonally coordinated phenanthroline. This platform facilitates a facile pathway for obtaining heteroleptic Cu­(I) complexes with the generic formula [Cu­(mesPhen)­(L)] + , where L is a second and distinct phenanthroline ligand (Chart ).…”
Section: Introductionmentioning
confidence: 99%